A new method for reducing the performance evaluation cost of the photovoltaic module cooling techniques using the photovoltaic efficiency difference factor. (October 2020) - Sultan, Sakhr M.; Tso, C.P.; Ervina Efzan, M.N.
Abstract: In an earlier work, a temperature-dependent photovoltaic efficiency difference factor, FTDED, was introduced for the purpose of evaluating the performance of the photovoltaic module (PV) cooling technique. The evaluation is achieved by indicating if the PV cooler performance is contributing to the photovoltaic efficiency gain or loss. The existing method (FTDED ) is costly because of the use of a fixed solar radiation of 1000 W/m 2, that is the solar radiation at PV's standard test conditions, and the involvement of one unit of a PV without a cooling technique that has the same number of solar cells as a PV with a cooler which are required to accomplish the performance evaluation. To solve the performance evaluation cost issue, a new method is proposed. This method can execute the performance evaluation of the PV coolers as the existing method but under various solar radiation values. It also depends on the output power of a PV with a single solar cell only (without a cooler) when conducting the performance evaluation for a PV with a cooler that has a known number of solar cells. The applicability conditions of the proposed method are illustrated. It is shown that the performance evaluation cost of PV cooling techniques can be greatly reduced. It can be concluded that the new method is a cost-efficient as compared with the existing method. PV cooling techniques designers and manufacturers are the potential users of the proposed method.